High fertility level in Sub-Saharan Africa: implication for reaping and optimizing demographic dividend - Sunmola, Adebayo K.; Olaosebikan, Johnson S.; Adeusi, Temitope J. (International Journal Of Community Medicine And Public Health, 2020)
Africa region remains the continent with the highest total fertility rate among other major regions of the world such as Europe, North America, Asia and Latin America and Oceania. This paper examines the determinants of high fertility in sub-Saharan Africa; it also determines the policy implication for reaping and optimizing demographic dividend. Secondary data sources were employed in achieving the set objectives. This paper submitted that determinants such as age at first marriage; high child mortality; low female education; gender preference; and limited birth spacing were the determinants of high fertility in Africa. For Africa to harness the demographic dividend, certain policy implications such as investment in child survival and health programmes; investment in quantity and quality of education; multi-sectoral approaches and meeting infrastructural development; enhance job market and enact and enforce laws to prevent early marriage among other policy programmes must be embraced. The paper concludes that there is high fertility in sub-Saharan Africa because of the in-built population momentum of the populace. Also, fertility must be reduced significantly if sub-Saharan Africa must reap and optimize the promising dividend. This paper, therefore, recommends that all government in Africa continent should come up with and implement effective population policy that will help to reduce high fertility level.